Regional geographies and public health lessons of the COVID-19 pandemic in the Arctic. - Tiwari, Sweta; Petrov, Andrey N; Golosov, Nikolay; Devlin, Michele; Welford, Mark; DeGroote, John; Degai, Tatiana; Ksenofontov, Stanislav (Frontiers in Public Health, 2023)
This study examines the COVID-19 pandemic's spatiotemporal dynamics in 52 sub-regions in eight Arctic states. This study further investigates the potential impact of early vaccination coverage on subsequent COVID-19 outcomes within these regions, potentially revealing public health insights of global significance.